PENGARUH TEKNIK PROBLEM SOLVING DALAM MENINGKATKAN KEBIASAAN BELAJAR SISWA - Zain Irwanto (Universitas Negeri Makassar, 2016)
The purpose of this study is to obtain a description of student learning habits in SMA Negeri I pangkep, and to determine whether there is influence problem solving techniques in improving student learning habits. This research comparative research is experimental. The sample of research class XI IPS 1 and XI IPS 2 were 32 students. Data collection technique with questionnaire while data analysis used is descriptive analysis, Barleth test and inferential statistical analysis with t-test formula. The results obtained are: the level of student learning habits in SMA Negeri I pangkep Pretest results both the experimental group and the average control group is low. After doing problem solving technique for experiment group, Postest value showed increase of study habits become high, while for control group of Postest value did not show improvement or remain in low category. Similarly, there are differences in learning habits between students who were given problem solving techniques with students who were not given problem solving techniques in SMA Negeri 1 pangkep. That is, for groups of students who are given problem solving techniques, student learning habits show improvement compared with groups of students who are not given problem solving techniques.